Career Development Human Resources for Education Institutions in Industry 4.0 Era: New Model Conceptual - Lolong, Rima Fien; Ebe, Lord Steward; Sumual, Tinneke E. M.; Sumual, Shelty D.M. (International Journal of Information Technology and Education, 2023)
HR career development has become an ongoing effort that requires commitment from the entire organization. This helps improve employee retention, motivation, and performance and ensures the organization has the talent it needs to achieve its goals. This research introduces a new conceptual model for career development in Human Resources (HR). This model aims to integrate an innovative and holistic approach to managing employee career development. By considering factors such as rapidly evolving technology, changes in work paradigms, and changing organizational needs, this model provides a fresh and relevant view of how HR can play a key role in facilitating employee professional growth. The results of this research discuss key aspects of this new conceptual model, including talent assessment, integrated career planning, personalized training and development, and an approach focused on work-life balance. Through this concept, this research guides HR professionals and organizational leaders on how they can adapt career development strategies that are more effective and relevant to the dynamics of the modern world of work. In conclusion, this new conceptual model encourages HR transformation to support employee growth and achieve organizational strategic goals in an era that continues to change rapidly.